Drive force optimization of a pneumatically-driven Gifford-McMahon cryocooler by numerical modeling. Issue 1 (March 2020) - Lei, Tian; Zuev, Yuri L.; Bao, Qian; Xu, Mingyao
Abstract: Pneumatically-driven displacer mechanisms are widely used in Gifford-McMahon (G-M) cryocoolers. Particularly for large size G-M cryocoolers, this type of drive is preferable compared to the scotch yoke-type, as only a small motor is required for driving the rotary valve and, therefore, the entire cryocooler can be very compact. Though various numerical models of G-M cryocoolers have been presented in the past, modeling of the pneumatically-driven type and optimization of the driving force have rarely been done. This work presents a one-dimensional numerical model of a pneumatically-driven single stage G-M cryocooler running at 80 K and related studies. The transient model predicts the movement of the displacer and simulates the cryocooler performance simultaneously. An optimization of the drive force is implemented for the defined cryocooler operating at various speeds. It discovers that the driving force reshapes the P-V diagram effectively and has to be well designed according to the frequency to maximize the cooling capacity per mass flow rate.